Aset Visual Dalam Mendesain Situs Website Umkm Holymoly Parfum Menggunakan Metode Design Thinking - Musthofa Kamal; Pungky Arifianto; Mahimma Romadhona (Jurnal Sains Informatika Terapan, 2026)
This study aims to explain the process of collecting and organizing visual design assets in website design using Holymoly Parfum as a case study. The purpose of this research is to show how structured asset preparation can support the creation of a consistent and user-friendly website interface. The benefit of this study is to provide guidance for designers, especially in MSME website development, in preparing visual components before the design stage begins. The dataset used in this research consists of visual assets collected during the design process, including product photos, typography, color palettes, icons, layout grids, spacing systems, and interface components created in the design system. This research use design thinking method and qualitative descriptive method with a case study approach. Data were collected through observation of the design workflow, documentation of design assets, and analysis of user interface requirements. The results show that organizing visual assets into a structured system improves visual consistency, speeds up the layout design process, and makes future design modifications easier.